Atitudes de Enfermeiros nos Cuidados com Famílias no Contexto do Parto e Puerpério Imediato - Ribeiro, Jéssica Sâmia Silva Torres (2016)
Introduction: Family-Centered Healthcare has been adopted as a philosophy of care in nursing and means that nurses incorporate into their care the knowledge and conviction that families represent a constant in the life of their members. The investigated object was delimited from the healthcare practices of nurses in the context of childbirth and postpartum and the attitudes of these professionals toward familycentered care, supported by the following research question: What attitudes are adopted by nurses in the context of childbirth and postpartum concerning the importance of the family in the healthcare process? Objectives: To identify nurses’ attitudes about the importance of families in the healthcare process, in the context of childbirth and postpartum according to the dimensions of the IFCE-AE Scale (A Importância das Famílias nos Cuidados de Enfermagem – Atitudes dos Enfermeiros [Importance of Families in Nursing Care – Nurses’ Attitudes); To relate the attitudes of nurses about the importance of families in the process of childbirth and postpartum healthcare with the professional training time and the degree of the nurses; To describe the attitudes that contribute to and/or suggest the valuation of families in the healthcare practices of nurses. Method: Descriptive and correlational cross-sectional study, carried out in the Housing and Obstetric Center of two reference health institutions in the state of Maranhão assisting with childbirth and postpartum: Hospital Universitário Unidade Materno Infantil (HUMI/UFMA) and Marly Sarney Maternity. The population was composed of seventy-six nurses, using two questionnaires to collect the data: IFCE-AE Scale (referenced above) and the Academic Professional Questionnaire. Software Stata 12.1 and the Pearson Correlation and t-student tests were used for the statistical analysis of the data. Results: Nurses held supportive attitudes toward families, with the average of 74.5 points in the area of Family: conversational partner and coping resource were 35.6; in the area of Family: resource in nursing care was 30.8 points and in the area of Family: Burden, the average was 8.01 points. A weak correlation was verified between the number of the nurses’ post-graduate studies in the area of Family: Burden; among the nurses with post-graduate studies in ICU with the area of Family: conversational partner and coping resource and a negative correlation between the attitude of the nurse toward the family and the attainment of the Family Nursing degree upon graduation. Conclusion: It would be opportune on the part of the studied instituions to invest in continued focused education in family care practices, with courses that involve this theme. For educational institutions for nurses, changing curriculum that suits the reality found outside of the walls of universities is essential.